(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Patients satisfaction is used as an important indicator of quality care and is frequently included in healthcare planning and evaluation. “The aims of this study is to” To study patients’ satisfaction regarding the quality of nursing care of the center , identify the main dimensions of patients’ satisfaction regarding quality of nursing care. And determine the association between sociodemographic variables and patients’ satisfaction regarding quality of the nursing care. The study was conducted during the period from1stDecember 2013 to 1stmaye 2014. The design of this study is Descriptive cross-sectional facility based study. The study sample was 305 patients who were selected randomly. All of them actually participated in the study and completed face to face interviewed questionnaire prepared according to Likert scale and data was analyzed by SPSS. The results showed that participants were moderately satisfied with the quality of nursing care in National Center for Diabetes Endocrinology and Genetics ,by used different dimensions, The total satisfaction mean was (3.22), with higher satisfaction levels in the physical environment of the center (M = 3.85) than technical quality (M =3.20). Patients from both settings were less satisfied with the responsiveness and convenience (M = 2.88). Age, sex, marital status, level of education, income and the diagnosis show statistically significant effects on patients’ level of satisfaction. On the other hand duration of diabetes and current occupation did not show statistically significant effects on patients’ level of satisfaction. In conclusion, the present study concluded that reforming community health nursing care policies to place more attention on increasing the level of enhance of responsiveness skills of nursing to patients communication and the interpersonal aspects of the provided care could probably increase their satisfaction. Lack of experience and professional skills of nursing care staff, in addition to overload work and the huge number of diabetic patients, increase the need for intensive training for nurses, and the involvement of the patient in treatment plan.